Relative apical sparing in severe aortic stenosis: does it mean concomitant amyloid cardiomyopathy?. (3rd October 2022) - R Santos, R; Abecasis, J; Maltes, S; Mendes, G S; Guerreiro, S; Padrao, C; Freitas, P; Ferreira, A; Ribeiras, R; Andrade, M J; Cardim, N; Gil, V; et al.
Abstract: Background: Relative apical sparing (RAS) of left ventricular (LV) longitudinal strain (LS) is a red flag marker for the suspicion of amyloid cardiomyopathy. However, it has also been described in patients with severe aortic stenosis (AS). Aim: To assess the prevalence of RAS in patients with severe symptomatic AS referred for surgical aortic valve replacement (AVR), to evaluate its clinical significance and assess its presence after surgery. Methods: We prospectively studied 135 consecutive patients (age: 73 y [IQR 68–77 y], 49% men) with severe symptomatic AS – mean transaortic pressure gradient (AVmean): 60.9±17.7 mmHg; mean aortic valve area: 0.7±0.2 cm 2, referred for surgical AVR with no previous history of ischemic cardiomyopathy or other. Beyond 12 lead-ECG and transthoracic echocardiography (TTE), all patients underwent cardiac magnetic resonance (CMR) before surgery. RAS was defined by the ratio >1 of average LS at apical segments/sum of the average basal and mid LS at speckle tracking analysis. AVR with septal myocardial biopsy, for investigational purposes, was performed in 80 patients. AS severity indexes, LV remodeling and tissue characterization parameters were compared in both groups of patients, with and without RAS. LS deformation pattern was reassessed at 3–6 months after AVR. Results: RAS was present in 24 patients (18%). In the whole cohort there were neither pseudoinfarct pattern or low voltage ECG criteria, nor infiltration suspicion from CMR (native T1 value 1053 ms [IQR 1025–1071 ms] for institutional reference values: 972–1070 ms; ECV 24% [IQR 21–27%]). None of the patients had amyloid deposition at histopathology. Overall, mean CMR LV ejection fraction (LVEF) was 59.6±10.5% and 98 patients (74%) had non-ischemic delayed enhancement, with a median fibrosis fraction of 4.1% [IQR 1.6–7.8%]. RAS cohort had a significantly higher AVmean gradient, relative wall thickness, maximum septal thickness, peak systolic dispersion, with lower global LS at TTE, as well as higher LV mass and lower LVEF at CMR. RAS group has also higher NT-proBNP ambulatory values (Table 1). Follow-up evaluation after AVR revealed RAS disappearance in 19 patients (79.2%). Conclusions: RAS occurs in almost one-fifth of the patients in this cohort despite the absence of signs of myocardial infiltration. This deformation pattern elapses with worse indexes of LV remodeling consistent with a more advanced stage of the disease, being reversible after AVR, which stands for the absence of concomitant myocardial infiltration. Funding Acknowledgement: Type of funding sources: None.